The prelimbic cortex uses higher-order cues to modulate both the acquisition and expression of conditioned fear - Sharpe, Melissa J.; Killcross, Simon (Frontiers in Systems Neuroscience, 2015)
The prelimbic (PL) cortex allows rodents to adapt their responding under changing experimental circumstances. In line with this, the PL cortex has been implicated in strategy set shifting, attentional set shifting, the resolution of response conflict, and the modulation of attention towards predictive stimuli. One interpretation of this research is that the PL cortex is involved in using information garnered from higher-order cues in the environment to modulate how an animal responds to environmental stimuli. However, data supporting this view of PL function in the aversive domain are lacking. In the following experiments, we attempted to answer two questions. Firstly, we wanted to investigate whether the role of the PL cortex in using higher-order cues to influence responding generalizes across appetitive and aversive domains. Secondly, as much of the research has focused on a role for the PL cortex in performance, we wanted to assess whether this region is also involved in the acquisition of hierarchal associations which facilitate an ability to use higher-order cues to modulate responding. In order to answer these questions, we assessed the impact of PL inactivation during both the acquisition and expression of a contextual bi-conditional discrimination. A contextual bi-conditional discrimination involves presenting two stimuli. In one context, one stimulus is paired with shock while the other is presented without shock. In another context, these contingencies are reversed. Thus, animals have to use the present contextual cues to disambiguate the significance of the stimulus and respond appropriately. We found that PL inactivation disrupted both the encoding and expression of these context-dependent associations. This supports a role for the PL cortex in allowing higher-order cues to modulate both learning about, and responding towards, different cues. We discuss these findings in the broader context of functioning in the medial prefrontal cortex.